Democratic Institutions and Subjective Well-Being. (October 2017) - Altman, David; Flavin, Patrick; Radcliff, Benjamin
We examine how differences in how democracy is institutionalized affect life satisfaction across nations. To our knowledge, this is the first rigorous, systematic study of this subject. Using data for 21 Organization for Economic Co-operation and Development (OECD) countries from 1981 to 2008, we find robust evidence that citizens report living more satisfying lives in countries with a parliamentary (rather than presidential) executive, a proportional representation electoral system (as opposed to single member districts), and a unitary (rather than federal) governmental structure. Moreover, the findings suggest that the real-world consequences for these types of democratic institutions for human well-being are substantial, rivaling or exceeding other common predictors. We conclude with a discussion of the practical and theoretical implications of the results.